The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.54589/aol.34/2/156
|View full text |Cite
|
Sign up to set email alerts
|

Dental fluorosis severity in children 8-12 years old and associated factors

Abstract: The aim of this study was to determine the frequency and severity of dental fluorosis (DF) and the association between severity and risk factors. In a cross-sectional study, 8- to 12-year-old children, born in a Colombian district, were evaluated according to the Thylstrup and Fejerskov Index (TFI) by two calibrated examiners. Molar Incisor Hypomineralization (MIH) and dental caries (DC) were also evaluated. Ordinal logistic regression was applied p<0.05). Risk factors and lifestyle factors were collected u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
1
0
7
Order By: Relevance
“…The effect of gender on the incidence of DF has not been investigated yet. An epidemiological survey of 929 adolescents in Northern Colombia revealed that the prevalence of DF did not differ significantly between the two genders and that it had no significant effect on the incidence (Saldarriaga et al, 2021b), which is consistent with the results of another survey of 1,044 adolescents in India (Verma et al, 2017). However, notably, economically underdeveloped areas and the unequal status of different genders can cause differences in the diet and living habits of people, which may contribute to the differences in its prevalence.…”
supporting
confidence: 77%
“…The effect of gender on the incidence of DF has not been investigated yet. An epidemiological survey of 929 adolescents in Northern Colombia revealed that the prevalence of DF did not differ significantly between the two genders and that it had no significant effect on the incidence (Saldarriaga et al, 2021b), which is consistent with the results of another survey of 1,044 adolescents in India (Verma et al, 2017). However, notably, economically underdeveloped areas and the unequal status of different genders can cause differences in the diet and living habits of people, which may contribute to the differences in its prevalence.…”
supporting
confidence: 77%
“…Mixed results were observed in different studies on the gender-wise occurrence of dental fluorosis in children as discussed by Akuno et al [ 17 ]. Studies by Keçeci et al [ 18 ], Saldarriaga et al [ 19 ], and Verma et al [ 20 ] showed no relationship between gender and fluoride effect on teeth, while some other studies showed significant gender differences in the prevalence of teeth fluorosis. In the present study, more prevalence was observed in girls than in boys.…”
Section: Discussionmentioning
confidence: 99%
“…La fluorosis dental o hipoplasia adamantina por factores ambientales o dientes moteados, es una alteración que produce discromías anormales en el esmalte dental (Saldarriaga et al, 2021). Se produce por la ingesta indiscriminada de fluoruros y por periodos prolongados, generando líneas blancas delgadas en la pieza dental hasta defectos anatómicos graves (James et al, 2021).…”
Section: Fluorosisunclassified

Eficacia De Los Fluoruros Para La Prevención De Caries Dental: Una Revisión Narrativa

Marisel Valenzuela Ramos,
Gustavo Canales Sermeño,
Juan Alvarado Figueroa
et al. 2023
HYW